Analyses of HR changes during competitive rowing - Batchev, V.; Neykov, S.; Kaloupsis, S.; Diafas, V. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Analyses of measured data showed that over 10% of HR data are in interval of 180-190 beats per minute and over 80%- interval 190-200.the maximal score of 198 beats were found. Summary HR changes during the competitive rowing are in diapason of 180-200 betas per minute and this formed one objective basic of structuring, characteristics and assessment of competitive loads of elite rowers.